Usability and adaptability of personal mobile devices (pmd) for street vendors with physical impairments - Kamaruddin, Zumahiran; Ab Jalil, Nurlelawati (International Journal for Studies on Children, Women, Elderly And Disabled (IJCWED), 2018)
Persons with physical impairments have limited regenerative abilities and mostly limited to some scope that they are able and unable to do and their participation in the activities are restricted and they are unemployed due to these limitations. Most of employees are afraid to take disabled people to work because of their limitation of accessibility. As an alternative, they could enjoy independent life, for example by venturing into small-medium entrepreneur sector. Persons with physical impairments usually rely on personal mobile devices to move and many forms of the device have been introduced to overcome their difficulties. However, the usability of the devices and the ability of the users to adopt the devices are uncertain. This research aims to understand the potential of using a mobile device as an independent assistant for the users, especially for the street vendors with physical impairments. The objective of the research is to determine the potential criteria of usability of mobile devices for working environment of the vendors in small medium entrepreneur sector. The discussions are based on reviews of related researches and literatures from different sources that were published over the past decade. The data also were collected by interviewing a group of people with physical disability and on-site observation. A group of personal mobile devices was identified including independent wheelchair assistant, motorized wheelchair and mobility scooter. The study found that the independent wheelchair assistant and motorized wheelchair are accommodative in making sure the user is fully independent. Although the device helps users independently access their local communities in some way, but there were several potential usability requirements and adaptability need to be explored. This study is significant in determining the functionality and usability of the device for various situation and places. Hence, further research to formulate design guidelines for the assistant mobile device for street vendor with physical impairment is exigency.